Two-criteria technical and economic optimization of forest transportation problem - Bazarov, S; Belenkiy, Yu; Sokolova, V; Solovyev, A (IOP conference series. Earth and environmental science, 2019)
The systematic analysis of optimizing the producer-consumer structure transportation problem is carried out in paper. It is in demand for the timber industry complex. The well-known minimum transportation cost objective is solved as a static problem using the linear programming method. Due to complicated market development conditions, it is necessary to set up and solve the problem of minimizing transportation time (quick performance) as a dynamic problem. Solving it in general case, the transportation cost may be different from the minimum cost determined by the static problem solution. The dynamic problem solution is based on the carrier's vehicle performance information used for determining the functional time spent per transported product unit. The rational decision making under market conditions is only possible by adopting a compromise obtained on the basis of the multi-criteria optimization theory. The task of determining the compromise area of two-criteria optimization (cost-time minimum ratio) is decided by experts. It is solved using the linear programming method for static and dynamic problems and their linear approximation. To develop a compromise transportation plan becomes the subject of solving the inverse transportation problem. The systemic "producer - transport - consumer" approach is necessary for sustainable timber industry complex development, when the producer-transport system makes up a single production process. Its parameters are determined on the basis of systems theory.